The Provision of Conceptual Change Text for Reducing Students’ Misconceptions in The Physics Learning of Light During the Pandemic Covid-19 - Tomo Djudin; Febriana Yuragi; Hamdani Hamdani (STKIP Singkawang, 2023)
Conceptual change is seen as a powerful teaching approach for developing 21st century skills. To determine the usefulness of delivering a conceptual change text for fostering conceptual change regarding light in physics learning at home during the pandemic, a quasi-experimental design was adopted, with one group pre-and posttesting. The participants are 23 eighth-grade students from SMPN 2 Ledo Bengkayang, a public secondary school in the rural region, who were recruited using an intact group random selection technique. A diagnostic test was provided, which included nine multiple-choice items and two distractors, as well as supporting arguments. This study discovered that students' beliefs regarding light and the process of vision vary significantly. After treatment, pupils' misunderstandings were reduced by 26.80%. After receiving the CCT, students had a considerable conceptual shift, and the CCT's effectiveness was sufficient (gain mean = 0.58). To get more effective results, CCT should be used in conjunction with any other teaching approach or model. A scientific teacher should exemplify a conceptual transformation method in the classroom.